SOME THEORETICAL ISSUES OF THE TRANSFORMATION OF THE SYSTEM OF PRINCIPLES OF ADMINISTRATIVE LAW (Bulletin of criminological association of Ukraine, 2023)
The article substantiates that despite the fact that the principles of administrative law of European states are generally stable in their legal nature they have constantly adapted to the modern conditions of the functioning of the EU, which is evolving as an organizational and legal structure. The European administrative space is rebuilt with the help of a set of general administrative principles, which are the standards of institutional construction in countries that are or wish to become full members of the European Union.It is noted that the legal systems of the EU member states are in the process of constant convergence with many different areas that are under the influence of EU legislation, for example, through the legislative activity of the institution
Keywords: system of principles; Administrative Law; transformation; concepts